2002
DOI: 10.1111/j.1945-5100.2002.tb00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Martian meteorite Dhofar 019: A new shergottite

Abstract: Abstract-Dhofar 019 is a new martian meteorite found in the desert ofOman. In texture, mineralogy, and major and trace element chemistry, this meteorite is classified as a basaltic shergottite. Olivine megacrysts are set within a groundmass composed of finer grained olivine, pyroxene (pigeonite and augite), and maskelynite. Minor phases are chromite-ulvospinel, ilmenite, silica, K-rich feldspar, merrillite, chlorapatite, and pyrrhotite. Secondary phases ofterrestrial origin include calcite, gypsum, celestite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
145
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(161 citation statements)
references
References 36 publications
15
145
1
Order By: Relevance
“…Other data sources included Dreibus et al (2000 for SaU 005 and Dhofar 378, Folco et al (2000) and Zipfel et al (2000) for Dar al Gani, Rubin et al (2000) for Los Angeles, Barrat et al (2001a, b) for NWA 480 and Dar al Gani, Jambon et al (2001) for NWA 856, and Taylor et al (2002) for Dhofar 019.…”
Section: Snc Meteorite Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Other data sources included Dreibus et al (2000 for SaU 005 and Dhofar 378, Folco et al (2000) and Zipfel et al (2000) for Dar al Gani, Rubin et al (2000) for Los Angeles, Barrat et al (2001a, b) for NWA 480 and Dar al Gani, Jambon et al (2001) for NWA 856, and Taylor et al (2002) for Dhofar 019.…”
Section: Snc Meteorite Datamentioning
confidence: 99%
“…On the other hand, one has less of a reason to suspect that REE (particularly La) and Th distributions have been altered significantly by terrestrial weathering effects (e.g., Dreibus et al 2001) and so these elements are considered more reliable for these samples. One caveat is the possible occurrence of small Ce anomalies (e.g., in Dhofar 019) suggestive of terrestrial weathering effects (Taylor et al 2002).…”
Section: Terrestrial Weathering Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…F) TiO 2 vs. MgO. Data are from Anand et al (2008), Dreibus et al (2000Dreibus et al ( , 2002, Gellert et al (2006), Gillet et al (2005), Ikeda et al (2006), Jambon et al (2002), , Neal et al (2001), Rubin et al (2000), Shirai and Ebihara (2004), Taylor et al (2002), Treiman et al (1986), Warren et al (1996Warren et al ( , 1999. .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have shown that shock-induced heating processes do not make olivine brown, because olivine from the highly metamorphosed terrestrial rocks is not brown (Treiman et al 2006, and references therein). Taylor et al (2002), Goodrich et al (2003), and Herd (2006) found that brown olivine from the Martian meteorites is equilibrated at oxidizing (e.g. NWA 1068) and reducing (e.g.…”
Section: Brown and Colorless Meteoritic Olivinementioning
confidence: 99%